Cytotoxic Steroids from The Stem Bark of Chisocheton cumingianus (Meliaceae) - Dewa Gede Katja; Kindi Farabi; Nurlelasari Nurlelasari; Desi Harneti; Euis Julaeha; Ace Tatang Hidayat; Tri Mayanti; Rani Maharani; Unang Supratman; Khalijah Awang (Molekul, 2017)
Three cytotoxic steroids, stigmasterol (1), stigmast-5-en-3b-ol (2) and b-sitosterol-3-O-acetate (3) were isolated from the stem bark of Chisocheton cumingianus. The chemical structures of those compounds were identified based on spectroscopic data and by comparison with those data previously reported. All of the compounds isolated were evaluated for their cytotoxic effects against P-388 murine leukemia cells in vitro. Compounds 1-3 showed cytotoxicity activity against P-388 murine leukemia cells with IC50values of 12.4, 60.8, and ÃÂ 100 mg/mL, respectively.